2021
DOI: 10.1038/s41598-021-97196-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic prediction by hypermetabolism varies depending on the nutritional status in early amyotrophic lateral sclerosis

Abstract: To examine whether hypermetabolism could predict the prognosis of early amyotrophic lateral sclerosis (ALS) patients with differing nutritional profiles. This single-center, retrospective study examined the prognosis of ALS patients with hypermetabolism in relation to their nutritional status at hospitalization. The metabolic state was estimated by the ratio of measured resting energy expenditure (mREE) to lean soft tissue mass (LSTM) (mREE/LSTM), wherein patients with ratios ≥ 38 were defined as hypermetaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…This discrepancy led us to formulate the BMI-muscle metabolism index (BMM index), defined as (BMI − 19.8) × (mREE/LSTM − 38); a high BMM index is an independent factor for poor prognosis. Furthermore, we showed that low body fat percentage was associated with poor prognosis 8 , as reported elsewhere 9 . These findings may indicate that the prognostic value of hypermetabolism depends on nutritional status and that lipid metabolism plays a crucial role in determining the prognosis of ALS.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…This discrepancy led us to formulate the BMI-muscle metabolism index (BMM index), defined as (BMI − 19.8) × (mREE/LSTM − 38); a high BMM index is an independent factor for poor prognosis. Furthermore, we showed that low body fat percentage was associated with poor prognosis 8 , as reported elsewhere 9 . These findings may indicate that the prognostic value of hypermetabolism depends on nutritional status and that lipid metabolism plays a crucial role in determining the prognosis of ALS.…”
Section: Introductionsupporting
confidence: 86%
“…), and LSTM (kg) was measured through a bioelectrical impedance analysis with a body composition analyzer (InBody S10; InBody, Tokyo, Japan). We used indirect calorimetry as reported previously 8 , 24 . In this study, as an indicator of the metabolic status, we used mREE/LSTM, which approximately reflects the skeletal metabolic status during the resting state; additionally, the relationship of this indicator with hypermetabolism was described in previous studies 4 , 25 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations